Complete mitochondrial genome of Clistocoeloma sinensis (Brachyura: Grapsoidea): Gene rearrangements and higher-level phylogeny of the Brachyura - Xin, Zhao-Zhe (Sci Rep, 2017)
Deciphering the animal mitochondrial genome (mitogenome) is very important to understand their molecular evolution and phylogenetic relationships. In this study, the complete mitogenome of Clistocoeloma sinensis was determined. The mitogenome of C. sinensis was 15,706 bp long, and its A+T content was 75.7%. The A+T skew of the mitogenome of C. sinensis was slightly negative (−0.020). All the transfer RNA genes had the typical cloverleaf structure, except for the trnS1 gene, which lacked a dihydroxyuridine arm. The two ribosomal RNA genes had 80.2% A+T content. The A+T-rich region spanned 684 bp. The gene order within the complete mitogenome of C. sinensis was identical to the pancrustacean ground pattern except for the translocation of trnH. Additionally, the gene order of trnI-trnQ-trnM in the pancrustacean ground pattern becomes trnQ-trnI-trnM in C. sinensis. Our phylogenetic analysis showed that C. sinensis and Sesarmops sinensis cluster together with high nodal support values, indicating that C. sinensis and S. sinensis have a sister group relationship. The results support that C. sinensis belongs to Grapsoidea, Sesarmidae. Our findings also indicate that Varunidae and Sesarmidae species share close relationships. Thus, mitogenomes are likely to be valuable tools for systematics in other groups of Crustacea.